Inclusive practice for special educational need care in Bucaramanga`s rural area - Pérez Pinzón, Luis Rubén (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The article considers a practical process of care for students with special educational needs, resulting from an inter-institutional research project, through which the Autonomous University of Bucaramanga’s specialized knowledge on disabilities and special education was integrated with innovative practices implemented by a rural institution in the Metropolitan area of Bucaramanga. Based on the description of three international models for theorizing and analyzing disabilities and special needs, we proposed an integral care and inclusion procedure. This procedure is characterized by six stages of integral and active education thought for students with both physical and motor special needs.